Decreases in self-reported alcohol consumption following HIV counseling and testing at Mulago Hospital, Kampala, Uganda - Hahn, Judith A.; Fatch, Robin; Wanyenze, Rhoda K.; Baveewo, Steven; Kamya, Moses R.; Bangsberg, David R.; Coates, Thomas J. (BMC Infectious diseases, 2014)
Alcohol use has a detrimental impact on the HIV epidemic, especially in sub-Saharan Africa. HIV counseling and testing (HCT) may provide a contact opportunity to intervene with hazardous alcohol use; however, little is known about how alcohol consumption changes following HCT. Methods: We utilized data from 2056 participants of a randomized controlled trial comparing two methods of HCT and subsequent linkage to HIV care conducted at Mulago Hospital in Kampala, Uganda. Those who had not previously tested positive for HIV and whose last HIV test was at least one year in the past were eligible. Participants were asked at baseline when they last consumed alcohol, and prior three month alcohol consumption was measured using the Alcohol Use Disorders Identification Test – Consumption (AUDIT-C) at baseline and quarterly for one year. Hazardous alcohol consumption was defined as scoring ≥3 or ≥4 for women and men, respectively. We examined correlates of alcohol use at baseline, and of hazardous and non-hazardous drinking during the year of follow-up using multinomial logistic regression, clustered at the participant level to account for repeated measurements. Results: Prior to HCT, 30% were current drinkers (prior three months), 27% were past drinkers (>3 months ago), and 44% were lifetime abstainers. One-third (35%) of the current drinkers met criteria for hazardous drinking. Hazardous and non-hazardous self-reported alcohol consumption declined after HCT, with 16% of baseline current drinkers reporting hazardous alcohol use 3 months after HCT. Independent predictors (p < 0.05) of continuing non-hazardous and hazardous alcohol consumption after HCT were sex (male), alcohol consumption prior to HCT (hazardous), and HIV status (negative). Among those with HIV, non-hazardous drinking was less likely among those taking antiretroviral therapy (ART).
Keywords: Alcohol; Africa; HIV; HIV counseling and testing; Antiretroviral therapy; Screening and brief intervention